Employment Status of Students from a Local University during the Covid-19 Pandemic - Angelito Bautista Jr; Araceli C. Suyat; Maria Aura C. Impang; Candice Erika J. Rudi; Bernard F. Gaya; Manuel Jr. M. Abiera; Gracia S. Josue (Universidade Estadual de Alagoas, 2023)
Working while taking classes is one of the most frequently cited reasons cited by university dropouts. As the Covid-19 pandemic has accelerated the adoption of teleworking by employers, online employment opportunities have increased. Given that the scenario allows students to work while studying online, determining the number and extent of employed students is an important area of research. This study aims to document the employment profiles of undergraduate students of Quezon City University. A total of 7,050 responses were received during the survey period. According to the findings of the study, approximately 15% of the students are employed full- or part-time. At the time of the survey, 64% of the working students who responded in the survey are working on-site, while 24% are working from home. Meanwhile, 50% of these working students are extremely satisfied with their current employment situation, while 44% are somewhat satisfied. In general, the majority of respondents are pleased with their current employment situation. Despite the fact that only two out of ten respondents are working students, the school administration must still pay close attention to this issue. The development of policies that will assist these students is required. For future studies, it is also important to examine employment patterns among undergraduates and how these patterns vary over time and based on student characteristics.